Technology at the Dining Table: Linking perceived value, service recovery, and continuous intention to use food delivery applications - Aslam, Wajeeha; Ham, Marija; Arif, Imtiaz (Review of Business Management, 2022)
Purpose – This study examined the influence of convenience, design, trustworthiness, price, and various food choices on the perceived value of food delivery applications. Furthermore, it investigated the role of perceived value and service recovery in the formation of attitudes and consumers’ continuous intention to use food delivery apps. Theoretical framework – The study used prior literature to develop a conceptual model of continuous intention to use food delivery apps. Moreover, the study further expands the model by considering the element of service recovery. Design/methodology/approach – The data were collected from users of food delivery apps that have previously faced some service failure issues. Using a sample of 380 respondents, the PLS-SEM technique was applied to test the hypotheses. Findings – The results showed that attitude and perceived value have a positive impact on continuous intention to use food delivery apps, whereas service recovery does not affect continuous intention to use them. However, both service recovery and perceived value have a positive impact on consumers’ attitudes towards food delivery apps. The results also revealed that all of the quality attributes of food delivery apps considered in the study positively affect the value perceived by the consumer. Practical & social implications of research – The findings of the study are beneficial for the food delivery businesses in terms of designing appropriate strategies aimed at developing consumers’ continuous intention to use food applications. It also contributes to the theory development by further complementing the framework with the service recovery factor. Originality/value – This is the first study to bring “service recovery” into the limelight in the context of food delivery apps. Moreover, it is the first study to establish a set of food delivery app quality attributes in a developing economy to determine perceived value, attitudes, and continuous intention to use such apps. Keywords – Food Delivery Apps, Continuous Intention, Attitudes, Service Recovery, Perceived Value, Various Food Choices.